2022
DOI: 10.1007/s10916-022-01850-y
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study on COVID-19 Lung Computed Tomography Segmentation with varying Glass Ground Opacities using Unseen Deep Learning Artificial Intelligence Paradigms: COVLIAS 1.0 Validation

Abstract: Variations in COVID-19 lesions such as glass ground opacities (GGO), consolidations, and crazy paving can compromise the ability of solo-deep learning (SDL) or hybrid-deep learning (HDL) artificial intelligence (AI) models in predicting automated COVID-19 lung segmentation in Computed Tomography (CT) from unseen data leading to poor clinical manifestations. As the first study of its kind, “COVLIAS 1.0-Unseen” proves two hypotheses, (i) contrast adjustment is vital for AI, and (ii) HDL is superior to SDL. In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 99 publications
0
6
0
1
Order By: Relevance
“…Similarly, the mean difference between the unseen and seen AUC for the EDL models was ~2.4% . Note that the criterion for a robust design, leading to superior generalizability, was that the difference between seen and unseen analysis be less than 3% to 5% [ 54 , 55 , 56 ]; our system design demonstrates results less than 3% , which qualifies it as a robust, generalizable, and stable design, which is also part of our running hypothesis.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, the mean difference between the unseen and seen AUC for the EDL models was ~2.4% . Note that the criterion for a robust design, leading to superior generalizability, was that the difference between seen and unseen analysis be less than 3% to 5% [ 54 , 55 , 56 ]; our system design demonstrates results less than 3% , which qualifies it as a robust, generalizable, and stable design, which is also part of our running hypothesis.…”
Section: Resultsmentioning
confidence: 88%
“…While individual deep learning models have shown limited success in detecting depression, combining them into hybrid deep learning models has been shown to improve performance and overcome data scarcity [ 50 ]. By leveraging multiple architectures, Hybrid models can address domain-specific challenges and improve accuracy in tasks such as detecting depression [ 51 , 52 , 53 , 54 ]. Using these spirits of HDL, we finally constructed three hybrid deep learning (HDL) models: a CNN-LSTM, a CNN-BiLSTM, and a BERT-BiLSTM.…”
Section: Methodsmentioning
confidence: 99%
“…GenAI aids in diagnostic accuracy, although its focus on higher value creation in health care is limited. The articles in this review reported that they used deep learning (34/161, 21.1%) [ 49 , 59 , 60 , 62 , 63 , 65 , 68 , 71 , 79 , 89 , 100 , 107 , 108 , 111 , 115 , 123 , 125 , 130 - 145 ], machine learning (9/161, 5.6%) [ 53 , 55 , 83 , 91 , 110 , 146 - 149 ], and image analysis approaches of GenAI during the assistance process (13/161, 8.1%) [ 68 , 88 , 104 , 110 , 111 , 114 , 116 , 119 , 133 , 135 , 138 , 150 , 151 ]. Knowledge access using GenAI has the potential to enable more options and flexibility in serving patients.…”
Section: Resultsmentioning
confidence: 99%
“…Deep learning (34/161, 21.1%) [ 49 , 59 , 60 , 62 , 63 , 65 , 68 , 71 , 79 , 89 , 100 , 107 , 108 , 111 , 115 , 123 , 125 , 130 - 145 ]…”
Section: Methodsunclassified
“…The use of DL algorithms allows the extraction of highly minute details that are not even visible to the human eye [26]. As a result, DL techniques are widely employed in medical image analysis for tasks including image registration [53], segmentation [54][55][56][57], and classification [58][59][60][61][62]. The most frequent type of brain tumor in people is glioma.…”
Section: Introductionmentioning
confidence: 99%